2006
DOI: 10.1007/s10549-006-9326-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for breast cancer in older women: the relative contribution of bone mineral density and other established risk factors

Abstract: Overall, BMD is a relatively weak predictor of breast cancer risk in these postmenopausal women with osteoporosis, after taking into consideration age, family history and endogenous estradiol level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 27 publications
3
20
0
2
Order By: Relevance
“…Our results are in line with several previously reported prospective and retrospective studies which revealed higher incidence of breast cancer in postmenopausal woman with higher BMD [2], [4]–[13], [15][17]. The majority of the reports originate from large databases such as the Rotterdam [6], Women’s Health Initiative (WHI) [5] and Framingham [16] studies or from pivotal trials in the field of osteoporosis (SOF, FIT, DOES) [2], [7], [9], that integrated data on BMD and breast cancer incidence in the same patient (2,4–7,9).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in line with several previously reported prospective and retrospective studies which revealed higher incidence of breast cancer in postmenopausal woman with higher BMD [2], [4]–[13], [15][17]. The majority of the reports originate from large databases such as the Rotterdam [6], Women’s Health Initiative (WHI) [5] and Framingham [16] studies or from pivotal trials in the field of osteoporosis (SOF, FIT, DOES) [2], [7], [9], that integrated data on BMD and breast cancer incidence in the same patient (2,4–7,9).…”
Section: Discussionsupporting
confidence: 93%
“…Others have shown that the positive relationship between BMD and breast cancer risk can be largely explained by effects of covariates and endogenous hormones such as age at menarche and menopause [13], [15]. In one study, an association between higher BMD and the risk for breast cancer was only observed in women with low estradiol level [15].…”
Section: Discussionmentioning
confidence: 99%
“…However, not all the studies have shown this relationship between BMD and breast cancer risk [22][23][24][25][26]. The San Francisco Mammography Registry was linked to regional BMD databases, and 15,254 women were identified who had a mammogram and BMD within 2 years of each other in a study examining whether breast cancer risk correlated with mammographic density and/or BMD [24].…”
Section: Discussionmentioning
confidence: 99%
“…A biológiai rendszer rendszeralgoritmusai is megváltoznak az élettartam emelkedésével, amelyek az ismert gerontológiai események feltárásával kerültek igazolásra. Így a környezetterhelésekkel megváltoztatott feltételen egy már módosult (lelassult, és alacsonyabb komplexitási kapacitású) működést prezentáló rendszernek kell a homeosztatikus egyensúlyt fenntartani [36,37]. Az, hogy a daganatos betegségek incidenciája és prevalenciája idősebb korban igazoltan kifejezettebb, a vázolt okokkal is magyarázható [34].…”
Section: Környezeti Alkalmazkodási Potenciál Csökkenés éS Egyes Biolóunclassified
“…öregedés [36,37]) és/vagy annak környezetében (környezetterhelések [5,6,7]) változások jelennek meg. Az említett változások lehetnek erőteljesek [32] és/vagy egyszerre több helyen kialakulók [33], amelyek következtében az alkalmazkodási kapacitás az adott organizmus esetében csökken, esetleg egy kritikus küszöbértéket is elér [4], ami következményesen a rendszer viselkedésének és/vagy állapotciklusának megváltozását indukálja.…”
Section: Megbeszélésunclassified